Introdução de um processo para medição de software em organização com nível inicial de maturidade - Jorge, Viviana Regina Weber (Universidade do Vale do Rio dos Sinos, 2013)
With the evolution of computer systems and the increasing dependence on information available at all times, software development and solutions that provide these facilities is bringing to light another need: the quality. The quality of the products that are delivered is vital in a world "moved to the technology". However, to ensure product quality, development methods used for this purpose must also be qualified. One way to have quality in the process of developing and software product is to control development practices. This control is made possible only through measurement methods that enable organizations to know their processes and identify points that need improvements, basing decision making. Thus, this work aims to propose a Software Measurement Process in organizations that have a low level of maturity in their processes, this is, so that they begin the introduction process aiming at the quality as soon as possible. And thus, obtaining benefits in order to seek higher levels of maturity, which may represent a market trend and need to maintain their competitiveness.
Keywords: Processo de medição; Processos de software; Métricas; Maturidade; Measurement process; Software processes; Metrics; Maturity